2014
DOI: 10.1080/10408398.2013.787969
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effect of Pesticides on Plant—A Review

Abstract: This review represents systematic and integrated picture of pesticide exposure to plant and its effect on growth and metabolism. Decades ago, agrochemicals were introduced aiming at enhancing crop yields and protecting crops from pests. Due to adaptation and resistance developed by pests to chemicals, every year higher amounts and new chemical compounds are used to protect crops, causing undesired side effects and raising the costs of food production. Biological chemical free agriculture is gaining also more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 88 publications
5
53
1
4
Order By: Relevance
“…Germination percentage of Mancozeb fungicide treated seed was decreased with the increase in concentration of fungicide Mancozeb. Other studies also reported that more fungicide produces negative interference and abiotic stress in germination of seeds and decreased it drastically in the treated sets (Horii et al 2007, Cataneo et al 2010, Marini et al 2011, Parween et al 2016. The results of our present study were conflict to Benicio (2015) who reported that fungicides doses not produces interference in germination of seeds.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…Germination percentage of Mancozeb fungicide treated seed was decreased with the increase in concentration of fungicide Mancozeb. Other studies also reported that more fungicide produces negative interference and abiotic stress in germination of seeds and decreased it drastically in the treated sets (Horii et al 2007, Cataneo et al 2010, Marini et al 2011, Parween et al 2016. The results of our present study were conflict to Benicio (2015) who reported that fungicides doses not produces interference in germination of seeds.…”
Section: Resultscontrasting
confidence: 90%
“…According to Anitha & Savitha (2013), Petit et al (2012) and Shakir et al (2016) chlorophyll content were also reduced after increasing the dose of Mancozeb fungicides. Majid et al (2014), Singh & Kaur (2016) and Parween et al (2016) reported oxidative stress caused by Mancozeb that affect overall plant growth as well as biochemical parameters especially chlorophyll content. It was also reported that higher dose of Mancozeb have negative effect on plant growth and activity of mycorrhizal symbiosis (Saleh 2006, Chaurasia 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, various approaches have been proposed to increase crop yields and to protect the growth of crops and vegetation under various environmental conditions, including extreme temperature changes and natural disasters [1][2][3]. Among the various approaches, those based on chemical materials have been mainly used in both crop cultivation and plant biology [4,5]. Chemical materials can provide nutrients to crops directly, and they can optimize the efficiency of the soil condition by increasing its water retention or modifying its aeration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, susceptible plants respond much the same as they do to other abiotic stresses . For example, suites of genes and enzymes of redox maintenance, xenobiotic metabolism and other protective pathways are recruited, likely as a result of signal transduction changes involving abiotic stress‐specific and other transcription factors (TFs). Repeated exposure to heat, cold, salt or other abiotic stresses can lead to systemic acquired acclimation (SAA), in which plants evolve enhanced stress resistance due to constitutive, enhanced expression of the genes noted above and others .…”
Section: Introductionmentioning
confidence: 99%